DIAGNOSIS AND PREVENTION OF MYOCARDIAL INFARCTION - Tursunov Feruz O’ktam o`g`li; Rakhmatov Jumanazar Abdurashid o`g`li (TADQIQOTLAR.UZ, 2024)
Abstract: This article discusses primary and secondary prevention of heart attacks. The doctor offers a number of methods and techniques. It is important to discuss the correct recommendations for patients during treatment and to eliminate problems that may arise during and after treatment. It also provides recommendations for cardiology professionals interested in teaching medical students these skills and applying them in practice.